Comparison of Helicobacter pylori Detection Methods: It’s Association with Leukocytosis and Monocytosis - Rahimkhani, Monireh; Mordadi, Alireza; Kazemian, Kiana; Khalili, Hourieh (Infectious Disorders - Drug Targets, 2020)
Background: Helicobacter pylori is a slow-growing micro-aerophilic gram-negative organism found in the stomach and duodenum. It is also associated with a number of stomach-duodenal diseases. Material and Methods: There are invasive and non-invasive methods to detect Helicobacter pylori infections. In a 13-months period, 101 patients with clinical signs of infection confirmed by biopsy and Rapid Urease test as well as a culture were included in this study. Results: There were significant correlations between breath urease test, anti-Helicobacter pylori serum IgG and IgA as well as fecal Helicobacter pylori Ag with the gold-standard method, (P=0.001) Moreover, there was a significant correlation between Monocytosis (P= 0.05) and goldstandard method. Conclusion: Based on studies conducted on patients with Helicobacter pylori infection, noninvasive diagnostics methods can be useful in the diagnosis of Helicobacter infections rather than evaluating anti-Helicobacter pylori serum IgM and also increased blood monocytes could be a reliable confirmation for detection. Furthermore, Monocytosis must be considered as a Helicobacter pylori infection at the first step in an area with a high infected percentage.
Keywords: Leukocytosis